Cladoceran diversity in Vinh Long province and redescription of the rare species Grimaldina brazzai richard, 1892 (Macrotricidae, Anomopoda, Branchiopoda) for zooplankton fauna Vietnam - Nga, Le Thi Nguyet; Phan, Dang Doan (Academia Journal of Biology, 2019)
In a total of four surveys at eight sites in some major rivers in Vinh Long province during 2013 to 2014, 18 species of cladoceran, belonging to 14 genera, 7 families and 2 orders, were recorded. The cladocerans fauna in Vinh Long province is recognized as moderate diverse, and the species recorded were mostly common species. Among 18 species, Grimaldina brazzai Richard, 1892 is a rare species. A total of four females specimens of species G. brazzai were collected at the Co Chien river, but male specimens were absent. The specimens were morphologically identified as G. brazzai described first by Richard (1892), followed by Brook (1959), Idris (1983), Smirnov (1992) and Hollwedel (2003). Grimaldina brazzai is currently the only one species in the genus Grimaldina and has been recorded in several tropical countries, such as Brazil, Thailand, Laos, Philippines, Indonesia, Malaysia, Cambodia and Singapore. They occur in lakes and rice fields, but population of this species is very limited in nature. In Vietnam, this species was first recorded in South Vietnam by Shirota (1966), but has not been described since then until recently Sinev & Korovchinsky (2013) recorded this species in the Cat Tien National Park, Dong Nai province, South Vietnam.